Evaluation systems and the pace of change – The example of Swedish higher education1. Issue 6 (11th May 2020) - Segerholm, Christina
Abstract: The aim of 1 this article is to illuminate and discuss evaluation and evaluation systems in relation to the pace of change. It is argued that evaluation promotes and accelerates change. The article will thus contribute to a critical scrutiny of evaluation as a societal phenomenon and as a widespread practice in education. To accomplish this aim, the inherent purpose of evaluation and evaluation systems is brought forward. National evaluation systems for Swedish higher education are used as an empirical example. An analysis using Rosa's three aspects of social acceleration (technical acceleration, acceleration of social change, and acceleration of the pace of life) is offered to demonstrate how the evaluation systems are related to, sustain, and promote an increase of the pace of change (acceleration) in educational practice in higher education.